Extrapancreatic insulinoma - Garg, Robin; Memon, Saba; Patil, Virendra; Bandgar, Tushar (World Journal of Nuclear Medicine, 2020)
A 38-year-old female presented with recurrent episodes of hypoglycemia for 5 years. On 72-h fast test, critical sample biochemistry was suggestive of endogenous hyperinsulinemic hypoglycemia. Both constrast-enhanced computed tomography and 68Ga-DOTATATE positron emission tomography/computerized tomography (PET/CT) revealed no pancreatic lesion but showed a jejunal lesion suggestive of neuroendocrine tumor (NET) but not confirmatory of insulinoma. 68Ga-Exendin-4 PET/CT showed intense uptake in the proximal jejunum, and this being a specific scan for insulinoma, confirmed it as an ectopic insulinoma. The patient attained normoglycemia after excision of this NET confirming it to be a case of ectopic insulinoma located in the jejunum. Although most insulinomas are located in the pancreas, rarely ectopic cases have been described in the spleen, perisplenic tissue, duodenohepatic ligament, adjacent to the ligament of Treitz, duodenum, and the jejunum. Functional scanning with 68Ga-Exendin-4 PET/CT scan aids the localization of ectopic insulinoma.
Keywords: 68Ga-Exendin-4 positron emission tomography/computerized tomography; 68Ga-DOTATATE positron emission tomography/computerized tomography; ectopic jejunal insulinoma